Of Gods and Kings: Ashur Imagery in Nahum - Cook, Gregory (Bulletin for biblical research, 2019)
Despite recognizing allusions to Ishtar in Nahum, commentators have not discussed the presence of Ashur imagery in the book. This article contends that Nah 3:18 identifies Yhwh’s ambiguous single male adversary as Assyria’s war god, Ashur. The phrase (3:18) is multivalent, referring to both the “king of Assyria” and “King Ashur.” When the verse is read in light of Assyrian inscriptions, it taunts Ashur that the human kings of Assyria no longer perform the duties assigned to them: shepherding and gathering the god’s people. The prophet, therefore, prophesied more than just Assyria’s demise; he also vilified the religion behind it.